A Video-Based Intervention on and Evaluation of Nursing Aides' Therapeutic Communication and Residents' Agitation During Mealtime in a Dementia Care Unit. Issue 4 (1st October 2016) - Levy-Storms, Lené; Harris, Lesley M.; Chen, Xiao
ABSTRACT: The researchers conducted a communication training intervention for certified nursing assistants (CNAs). The intervention aimed at improving CNAs' therapeutic techniques for relating to agitated residents during care. This study focused on an in-depth evaluation of mealtime interactions using videos. Sixteen CNAs and 16 residents living with dementia from one long-term care facility were videotaped during mealtime interactions before and after a therapeutic communication training program. Mixed-effect Poisson regression revealed no effect of the intervention as a whole on residents' refusals, but the intervention did improve CNAs' communication. Additional analyses using specific CNAs' therapeutic communication behaviors indicated a significant negative association with refusals at post-test but not pretest. The findings suggest some communication mechanisms for how the intervention positively influenced residents' refusals.